2017
DOI: 10.1155/2017/8434281
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative Success Rate of Short and Ultrashort Implants Supporting Single Crowns in the Posterior Maxilla: A 3-Year Retrospective Study

Abstract: Aim To determine cumulative success rate (CSR) of short and ultrashort implants in the posterior maxilla restored with single crowns. Patients and Methods We performed a retrospective study in 65 patients with 139 implants. 46 were ultrashort and 93 short. Implants were placed with a staged approach and restored with single crowns. Success rate, clinical and radiographic outcomes, and crown-to-implant ratio (CIR) were assessed after three years. Statistical analysis was performed by descriptive and inferential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(64 citation statements)
references
References 46 publications
2
59
0
3
Order By: Relevance
“…[21][22][23] In addition, some clinicians preferred short implants rather than conventional implants with bone augmentation in terms of time, cost, and morbidity. In contrast, more recently published systematic reviews have found short implants to exhibit similar survival and success rates to conventional implants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] In addition, some clinicians preferred short implants rather than conventional implants with bone augmentation in terms of time, cost, and morbidity. In contrast, more recently published systematic reviews have found short implants to exhibit similar survival and success rates to conventional implants.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, more recently published systematic reviews have found short implants to exhibit similar survival and success rates to conventional implants. [21][22][23] In addition, some clinicians preferred short implants rather than conventional implants with bone augmentation in terms of time, cost, and morbidity. 24,25 In this study, the proportion of failed implants in sample group of short implants is relatively higher than that of conventional implants, suggesting that short implant has been evaluated as a risk factor.…”
Section: Discussionmentioning
confidence: 99%
“…Disain yang datar yang dimiliki oleh sistem implan Bicon sangat unik, yaitu dengan menggunakan prinsip Bioengineering dengan menciptakan Implan SHORT, yaitu implan yang pendek (5-6mm) kurang lebih 30% lebih kecil dibandingkan dengan implan yang berjenis ulir (screw) dan memiliki dimensi yang sama dengan implan lainya untuk membuat ikatan tulang yang baru diantara ulir (fins) implan. 7,23 Permukaan sistem implan Bicon dibuat dengan cara grit blasted dengan alumina dan dibilas oleh larutan asam nitrat yang disebut Integra-Ti. Umumnya insersi implan berjenis ulir dilakukan dengan kecepatan 800-1200 rpm dengan irigasi tetapi pada implan sistem Bicon pengeburan dilakukan sebesar 50 rpm tanpa irigasi sehingga mudah mengambil sisa tulang dari hasil pengeburan tersebut.…”
Section: Desain Implan Yang Beredar DI Pasaran Dan Fungsinyaunclassified
“…Umumnya insersi implan berjenis ulir dilakukan dengan kecepatan 800-1200 rpm dengan irigasi tetapi pada implan sistem Bicon pengeburan dilakukan sebesar 50 rpm tanpa irigasi sehingga mudah mengambil sisa tulang dari hasil pengeburan tersebut. 7,14,23 Struktur makro dan mikro permukaan SLA (Sandblasted Large Grit Acid Etching) saat ini menjadi standar emas dalam teknologi implant terkini. Teknologi permukaan tersebut dapat mempercepat waktu penyembuhan menjadi 3-4 minggu.…”
Section: Desain Implan Yang Beredar DI Pasaran Dan Fungsinyaunclassified
“…Nessa mesma linha de raciocínio, um recente estudo 28 considerou implantes > 8mm como longos, < 8mm como curtos e < 6mm como ultracurto. Outros dois estudos 15,[29][30] consideraram a nomenclatura de extra curto implantes com altura <5mm. Essa classificação baseou-se no fato de que a taxa de sobrevida de implantes <8mm foi diferente dos >9mm 26 .…”
Section: I S C U S S ãOunclassified